Pendekatan Tunai dan Nontunai Dalam Pengentasan Kemiskinan di Indonesia - Odit Mukti Pratomo; Safitra, Dhian Adhetiya (Politeknik Keuangan Negara STAN, 2021)
Poverty alleviation programs have become a sustainable policy agenda in Indonesia, whether carried out during the Covid-19 pandemic or before. This poverty alleviation program can take the form of cash or in-cash social assistance. The main objective is to increase the purchasing power of low-income families for necessities. With SUSENAS 2016 data, this study found that cash assistance (in the form of the Family Hope Program) and non-cash assistance (in the form of Prosperous Rice) did not consistently affect low-income families consumption. This finding can consider that the objectives or implementation of policies to increase consumption need to evaluated. Keywords: poverty alleviation programs, covid-19 pandemic, power of low-income families, cash assistance, increase consumption